2022
DOI: 10.1162/jocn_a_01874
|View full text |Cite
|
Sign up to set email alerts
|

A Special Role of Syllables, But Not Vowels or Consonants, for Nonadjacent Dependency Learning

Abstract: Successful language processing entails tracking (morpho)syntactic relationships between distant units of speech, so-called nonadjacent dependencies (NADs). Many cues to such dependency relations have been identified, yet the linguistic elements encoding them have received little attention. In the present investigation, we tested whether and how these elements, here syllables, consonants, and vowels, affect behavioral learning success as well as learning-related changes in neural activity in relation to item-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 130 publications
0
7
0
Order By: Relevance
“…A potential reason for this challenge may be that by the age of 8–10 months (or earlier), infants have learned to group individual sounds into syllabic units. Similar to adults, who display a clear advantage for syllable-based NAD learning ( Weyers and Mueller, 2022 ), infants at this age may perceive syllables as more salient than individual phonemes. The fact that there was a pause inserted between syllables in the present experiment might have supported syllable instead of phoneme perception.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…A potential reason for this challenge may be that by the age of 8–10 months (or earlier), infants have learned to group individual sounds into syllabic units. Similar to adults, who display a clear advantage for syllable-based NAD learning ( Weyers and Mueller, 2022 ), infants at this age may perceive syllables as more salient than individual phonemes. The fact that there was a pause inserted between syllables in the present experiment might have supported syllable instead of phoneme perception.…”
Section: Discussionmentioning
confidence: 81%
“…Interestingly, the same paradigm with adults yielded (besides a strong syllable advantage for NAD learning) an electrophysiological (but no behavioral) indication of learning based on consonants, but not vowels ( Weyers and Mueller, 2022 ), even though an advantage for vowels in structural processes has been argued to be present in adults as well (e.g., Bonatti et al, 2005 ). One reason could be that adults already have extensive experience with possible words and grammatical relations in their native (and non-native) language(s).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The results showed that a substantial increase in spelling achievement for both the closed syllable spelling test and the silent syllable spelling test. Other studies with positives views towards the syllabary method include [16,17,18,19,20,21,22] Latifa Belfakir, Ph.D., has been working as a university professor for 19 years. Her major fields of interests, as a researcher, are technology and language teaching and Leadership studies.…”
mentioning
confidence: 99%